Assessing the Role of Entrepreneurship Education in Reducing Youth Unemployment in Onitsha North Local Government Area, Nigeria - Ann Ngozi Ugobueze (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
This literature review examines the influence of entrepreneurship education on youth employment and skill development based on findings synthesized from peer-reviewed research published within the last decade. The review draws on studies conducted primarily in developing countries, particularly sub-Saharan Africa with a focus on Nigeria, retrieved from academic databases such as Google Scholar, ERIC, JSTOR, and ResearchGate using keywords including “entrepreneurship education,” “youth employment,” “skill acquisition,” and “economic empowerment.” The review reveals that entrepreneurship education significantly enhances youth employability by fostering entrepreneurial intentions, promoting self-employment, and reducing dependence on limited formal job opportunities. It also contributes to the development of vocational, technical, and managerial skills relevant to the labor market. However, its effectiveness is constrained by limited institutional support, inadequate funding, lack of qualified instructors, and theoretical-oriented instructional approaches. Overall, the literature indicates that entrepreneurship education plays a strategic role in economic and social empowerment of youth when effectively implemented, and calls for curriculum reform, practical-based training, and stronger school–industry partnerships to maximize impact.